Knowledge, attitudes, and practices towards prevention and control of neurocysticercosis-related epilepsy in Northern Tanzania: A cross-sectional healthcare professional-based study. - Masanja Laurent Lugelongi; Andrew Martin Kilale; Kabemba Evans Mwape (PLoS Neglected Tropical Diseases)
Background Infection of the brain with the larval stage of Taenia solium leads to neurocysticercosis (NCC), a leading cause of epilepsy with a considerable global burden. Neurocysticercosis-induced epilepsy is among the poverty-related diseases and is prevalent, particularly in regions where T. solium is endemic. In Tanzania, NCC-associated epilepsy is endemic, it causes substantial health burdens and economic losses. Studies on knowledge, attitudes, and practices (KAP) regarding NCC in the country are limited. Methodology A cross-sectional healthcare professional-based study was conducted in northern Tanzania between May and July 2023. A structured questionnaire was administered to healthcare workers (HCWs) using a random stratified sampling to assess their knowledge, attitudes, and practices toward prevention and control of NCC-induced epilepsy. One-way ANOVA was used to compare mean scores of KAP, Chi-square test to assess the association between independent factors and KAP scores, and logistic regression model to determine the predictors of KAP scores. Results A total of 250 HCWs were interviewed. The study revealed that HCWs had inadequate overall knowledge (scores = 55.5%), negative attitudes (score = 54.0%) and poor practices (scores = 49.3%). Only 22.4% had adequate knowledge, 10.8% had positive attitudes, and 12.8% had good practices towards control of NCC-induced epilepsy. Educational levels of respondents (OR: 3.361, 95% CI: 1.147-9.848, p < 0.01) were significant predictors of positive attitudes. Laboratory technologists were five (OR:5.821, 95% CI: 2.033-16.664, p < 0.01) times more likely to be knowledgeable, followed by assistant physicians (OR:3.141, 95% CI:1.484-6.650, p < 0.01) compared to other health professionals interviewed. Knowledgeable respondents were more likely to have positive attitudes (OR: 6.087, 95% CI:2.534-14.622, p < 0.01), and better practices (OR: 4.750, 95% CI: 2.099-10.748, p < 0.01) towards control of NCC-induced epilepsy. Conclusion This study found that HCWs had limited knowledge, poor practices, and negative attitudes toward the control of NCC-induced epilepsy. There is an urgent need to promote better knowledge of acquired epilepsy among HCWs, including re-training using the One Health approach in T. solium endemic areas.